COMMERCIAL INSTRUMENTALISATION OF MEDIA AND AUTONOMY OF PROFESSIONAL COMMUNICATORS IN THE MEDIA SYSTEM OF THE REPUBLIC OF SRPSKA - Kuprešanin Vukelić, Anđela (Politeia, 2021)
Commercial instrumentalisation of the media presents one of inevitable dimensions with regard to studying contemporary media systems. Researching into the level of commercial instrumentalisation of the media within a certain media system implies researching into the nature of relationship, that is, interaction of the media, professional communicators, and certain external information agents, such as advertisers and owners of capital. Instrumentalisation of the media for commercial purposes determines, to a great extent, the professional stance of communicators and their autonomy while performing the task of satisfying public interests in relation to the exclusively material orientation of media production, which is reflected on the quality of media contents and media pluralism. The paper examines the intensity and nature of interaction between the media and advertisers in the media system in the Republic of Srpska and implications of this interaction with regard to the journalist profession and media practice, from the point of view of journalists, editors, and media managers. As for the working hypothesis of the paper, the author claims that there are various forms of commercial instrumentalisation of the media in the aforementioned system that jeopardise, either directly or indirectly, the autonomy of professional communicators and meeting the necessary professional standards. For these purposes, the gathering of empirical material is realised by means of a survey poll engaging 150 journalists and 65 editors employed with 27 respective media companies in the Republic of Srpska, as well as by means of interviewing 10 media managers. The paper aims at identifying the forms and intensity of commercial instrumentalisation of the media in the media system of the Republic of Srpska which, apart from being of significance for the autonomy and professionalism of the media and communicators, are major indicators of the nature of the media system on the whole and which primarily determine the course of its transformation.